Nursing Implementation in PreSchool-Aged as an Effort to Improve Psychosocial Development Through Motor Stimulation and Language - Esti Mediastini; Livana PH (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Preschool aged children are children aged 3-6 years. At preschool age, the psychosocial development of children is obvious, because they have started to actively engage with their peers. The signs of psychosocial development at this stage are that the child begins to know the rules. The psychosocial development of children at the preschool stage will form the basis of a person's psychosocial condition as an adult. Genetic, environmental, and health factors can influence a child's development. One of the health factors that can affect a child's development is a history of using antipyretic drugs. The purpose of this study was to determine the psychosocial development of pre-school age children with a history of using antipyretic drugs before and after being given motor and language stimulation. The research was conducted in Kendal City. This study used a quasi-experimental design with pre post test with control group. The research measuring instrument used a questionnaire with validity and reliability and an observation sheet to measure psychosocial development in preschool children. The research sample consisted of 120 children who were divided into 2 groups. Data were analyzed univariately with central tendency and frequency distribution. While the bivariate analysis used the chi square test. The results showed that there were differences in psychosocial development in pre-school age children in the control group and the intervention group after providing language and motor stimulation with a value of p = 0.038 (p <0.05).